Is there a place for a biological mesh in perineal hernia repair? - Musters, G. D. (Hernia, 2016)
PURPOSE: This study aimed to determine the outcome of perineal hernia repair with a biological mesh after abdominoperineal resection (APR). METHOD: All consecutive patients who underwent perineal hernia repair with a porcine acellular dermal mesh between 2010 and 2014 were included. Follow-up was performed by clinical examination and MRI. RESULTS: Fifteen patients underwent perineal hernia repair after a median of 25 months from APR. Four patients had a concomitant contaminated perineal defect, for which a gluteal fasciocutaneous flap was added in three patients. Wound infection occurred in three patients. After a median follow-up of 17 months (IQR 12–24), a clinically recurrent perineal hernia developed in 7 patients (47 %): 6 of 11 patients after a non-cross-linked mesh and 1 of 4 patients after a cross-linked mesh (p = 0.57). Routine MRI at a median of 17 months revealed a recurrent perineal hernia in 7 of 10 evaluable patients, with clinical confirmation of recurrence in 5 of these 7 patients. No recurrent hernia was observed in the three patients with combined flap reconstruction for contaminated perineal defects. CONCLUSION: A high recurrence rate was observed after biological mesh repair of a perineal hernia following APR.